AGRIBUSINESS ANALYSIS OF USAHATANI CENGKEH (zysygium aromaticum. L) DIDESA COMMUNICATIONS IN LAROMPONG DISTRICT LUWU DISTRICT. ANALISIS AGRIBISNIS USAHATANI CENGKEH (zysygium aromaticum . L ) DIDESA KOMBA KECAMATAN LAROMPONG KAB - Darmawan (Jurnal Ilmiah Agrotani, 2019)
Agribusiness is an agriculture-based business or other field that supports it, both in the upstream and downstream sectors. Agricultural science is applied science that discusses or learns how to make or use resources efficiently. Clove is a kind of dried flower from the Syzygium aromaticum plant. Cloves have other names, cloves. Cloves are indeed flowers from tree myrtaceae This study aims to find out how Clove Farming in Komba Village, Larompong District, Luwu Regency. This research was conducted in June 2018 until August 2017. The informants in this study were clove farmers, the data collection techniques were carried out through observation, interviews, group discussions, documentation. The focus observed was the characteristics of clove farmers and informants, the data analysis used in this study was a type of qualitative analysis, the results of the study showed that Komba Village, Larompong District, Luwu Regency. Keywords : agribusiness,farming and clove